Nation’s rise and fall: A search for dynamics from Quranic perspective - Gilani, Sayyid Muhammad Yunus (2013)
The universe is created and regulated in a systematic way which makes it a cosmos and not a chaos. Everything here follows sunnatullah, the natural laws of cause and effect. Even the rise and fall of nations in time and space is governed by these divine laws. The Quran depicts the standards and virtues such as strong belief system, righteous deeds, justice, reformation, renewal,knowledge and wisdom that might raise a nation to the sublime position among the nations. Similarly, it refers to some factors such as luxury, injustice, religious extremism, disunity that could propel a nation from sublime to the ridiculous. For rise and fall, moral and material factors are equally important. Rise and fall are regulated by the Laws of Allah and subject to the norm of cause and effect. This paper explores the Qur’anic dynamics of a nation’s rise and fall. It highlights on how the divine law, sunnatullah, is functioning in this connection. It is expected that this study would deliver a significant contribution to this subject.